Feeding ecology of spotted scat scatophagus argus, linnaeus in mangrove forests Pak Phanang estuary, Nakhon Si Thammarat Province - Supichaya Wongchinawit (Chulalongkorn University, 2010)
Thesis (Ph.D.)--Chulalongkorn University, 2007